PENGARUH PENGGUNAAN MODUL HASIL PENELITIAN PENCEMARAN DI SUNGAI PEPE SURAKARTA SEBAGAI SUMBER BELAJAR BIOLOGI POKOK BAHASAN PENCEMARAN LINGKUNGAN TERHADAP HASIL BELAJAR SISWA - Purnomo, Dwito; Indrowati, Meti; Karyanto, Puguh (Pendidikan Biologi, 2013)
ABSTRACT ? The purpose of this research is to ascertain the influence of pollution in Pepe Surakarta river research module implementation as biology learning resource in environmental pollution subject material toward learning achievement. The research is belonged to quasi experiment with posttest only control design. The independent variable in this research is a module as biology learning resource and dependent variable is learning achievement. The populations of this research were all of 7th degree students at SMP Al Irsyad Surakarta in academic years of 2011/2012.  The samples of this research were the students of 7thA as experiment group and 7thC as control group. The sample of this research was established by cluster random sampling. The data was collected using questionnaire, essay test, observation form, and document. The hypotheses analyzed by t-test. The result of  t-test had been conducted the significant value (?) < 0,05 in all domains of learning out comes, So it can be concluded that implementation of research module as biology learning resource had significant effect toward learning achievement of 7th degree students at SMP Al Irsyad Surakarta in cognitive, affective, and psychomotor domains. Keywords: Research Module, Learning Achievement, Cognitive, Affective, Psychomotor.